2011
DOI: 10.1038/hdy.2011.123
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence, range expansion and possible homoploid hybrid speciation among pine species in Northeast China

Abstract: Although homoploid hybrid speciation in plants is probably more common than previously realized, there are few welldocumented cases of homoploid hybrid origin in conifers. We examined genetic divergence between two currently widespread pines in Northeast China, Pinus sylvestris var. mongolica and Pinus densiflora, and also whether two narrowly distributed pines in the same region, Pinus funebris and Pinus takahasii, might have originated from the two widespread species by homoploid hybrid speciation. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 64 publications
(89 reference statements)
1
28
0
1
Order By: Relevance
“…The pattern of rapid population growth in the Middle-Late Pleistocene predating the Last Glacial Maximum (LGM, 26.5-19 ka) could be explained by increasing aquatic habitats after the largest Quaternary glaciation in the Middle Pleistocene recorded in the East Asia (Zheng et al, 2002;Wu et al, 2002). Our findings add to a growing body of evidence suggesting recent population growth in the Middle-Late Pleistocene prior to the LGM, as found in freshwater fishes (e.g., Watanabe et al, 2010) and terrestrial organisms from East Asia (e.g., Ding et al, 2011;Ren et al, 2012).…”
Section: Glacial Refugia and Pleistocene Split Of Major Cladesmentioning
confidence: 63%
“…The pattern of rapid population growth in the Middle-Late Pleistocene predating the Last Glacial Maximum (LGM, 26.5-19 ka) could be explained by increasing aquatic habitats after the largest Quaternary glaciation in the Middle Pleistocene recorded in the East Asia (Zheng et al, 2002;Wu et al, 2002). Our findings add to a growing body of evidence suggesting recent population growth in the Middle-Late Pleistocene prior to the LGM, as found in freshwater fishes (e.g., Watanabe et al, 2010) and terrestrial organisms from East Asia (e.g., Ding et al, 2011;Ren et al, 2012).…”
Section: Glacial Refugia and Pleistocene Split Of Major Cladesmentioning
confidence: 63%
“…Similarly in northern and northeast China, phylogeographic studies suggest regional expansions and multiple glacial refugia for a limited number of species with glacial refugia being sparsely located in the mountains from the north to the south (e.g., Chen et al, 2008a; Du et al, 2009; Tian et al, 2009; Bai et al, 2010; Guo et al, 2010; Ren et al, 2011; Zeng et al, 2011; An et al, 2012). However, in middle, southern and southeast China, regional expansions were found rarely and only local expansions occurred in the studied species (e.g., Su et al, 2005; Wang & Ge, 2006; Gao et al, 2007; Yan et al, 2007; Qiu et al, 2009a, 2009b; Wang et al, 2009a; Zhou et al, 2010; Chen et al, 2012; Li et al, 2012c; Peng et al, 2012; Xiao et al, 2012; Xie et al, 2012).…”
Section: Phylogeographic Patterns Of Plants In Chinamentioning
confidence: 99%
“…Some studies have indicated that positive selection might have been involved in the adaptation of Pinus species to shifts in environmental conditions during their evolutionary and speciation processes (Ma et al, ; Ruhfel et al, ; Zhou et al, ). This type of information can provide valuable genetic resources for investigating the adaptive population history and interspecific divergence of closely related species (Ren et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%